Perceived and Actual Social Discrimination: The Case of Overweight and Social Inclusion - Hartung, Freda-Marie; Renner, Britta (Frontiers in Psychology, 2013)
The present study examined the correspondence between perceived and actual social discrimination of overweight people. In total, 77 first-year students provided self-ratings about their height, weight, and perceived social inclusion. To capture actual social inclusion, each participant nominated those fellow students a) she/he likes and dislikes and b) about whom she/he is likely to hear social news. Students with lower BMI felt socially included, irrespective of their actual social inclusion. In contrast, students with higher BMI felt socially included depending on the degree of their actual social inclusion. Specifically, their felt social inclusion accurately reflected whether they were actually liked/disliked, but only when they were part of social news. When not part of social news, they also showed insensitivity to their actual social inclusion status. Thus, students with a lower BMI tended to be insensitive, while students with a higher BMI showed a differential sensitivity to actual social discrimination.